Application for Selling Cuisine at Padang X Restaurant Based on Web - Maulina Nabila (Politeknik Siber Cerdika Internasional, 2020)
This Padang X restaurant was founded about 2 years ago, and is located on Jl. Pangeran No.136 Bekasi. This location is chosen because it is an area surrounded by offices such as village offices, sub-districts, and banks. So this place is a strategic place to be established restaurants. To provide good service to consumers, Padang X restaurant needs to know what is expected from consumers. In addition, X restaurant also needs to pay attention to the services provided to consumers so that if consumers are satisfied with the service they have received, consumers will still choose restaurants in Sabana Minang compared to other restaurants. So, the quality of service services is very important to note because it is closely related to consumer satisfaction Tekhnik data collection by looking directly at the survey to the field and dealing directly with activities that are directly involved in the sale of padang X restaurants.